2018
DOI: 10.1097/moo.0000000000000444
|View full text |Cite
|
Sign up to set email alerts
|

Detection of surgical margins in oral cavity cancer: the role of dynamic optical contrast imaging

Abstract: DOCI augments tissue contrast and may enable surgeons to clinically screen patients for oral cancer, make histologic evaluations in vivo with fewer unnecessary biopsies, delineate clinical margins for tumor resection, provide guidance in the choice of biopsy sites, and preserve healthy tissue to increase the postoperative functionality and quality of life of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…We have previously designed Dynamic Optical Contrast Imaging (DOCI), a novel imaging modality that acquires temporally dependent measurements of tissue autofluorescence. [5][6][7][8][9] Furthermore, we demonstrated that DOCI can distinguish HNSCC from adjacent healthy tissue with a high degree of accuracy. 5 DOCI images are captured in real time, offering an operatively wide field of view.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…We have previously designed Dynamic Optical Contrast Imaging (DOCI), a novel imaging modality that acquires temporally dependent measurements of tissue autofluorescence. [5][6][7][8][9] Furthermore, we demonstrated that DOCI can distinguish HNSCC from adjacent healthy tissue with a high degree of accuracy. 5 DOCI images are captured in real time, offering an operatively wide field of view.…”
Section: Introductionmentioning
confidence: 72%
“…[3][4][5] The methodology by which frozen section margins are collected-whether from the tumor bed or specimen itself-can also alter margin outcome. 6,7 Thus, improving intraoperative detection of tumor margins is critical to optimizing oncologic surgical treatment and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Spectroscopic methods such as elastic scattering spectroscopy and Raman spectroscopy have been also reported for in vivo discrimination of OSCC from surrounding normal tissue ( 11, 12 ), and fluorescence lifetime imaging (FLIM)–derived parameters combined with machine learning classifiers have shown promise in discriminating healthy margin tissue from OSCC ( 19 ). Another emerging approach is dynamic optical contrast imaging, which is another configuration of FLIM and maps fluorescence lifetime variations between OSCCs and margins ( 13 ). Microscopic imaging approaches include high-resolution micro-endoscopy, optical coherence tomography (OCT), and ex vivo fluorescence confocal microscopy ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…As has already been demonstrated by our previous studies and in the current one, DOCI reliably differentiates head and neck cancer tissue from surrounding normal tissue on the basis of fluorescence decay information. [5][6][7][8][9][10] The performance of the DOCI system is enhanced by the CNN-based classification model for automated classification of tumor and nontumor tissue of DOCI-acquired images. As the CNN model continues to acquire further DOCIacquired image samples, we anticipate that the tumor region confidence will continue to improve above the current 76.02% confidence mark.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has developed and previously described Dynamic Optical Contrast Imaging (DOCI), a novel imaging modality that acquires temporally-dependent measurements of tissue autofluorescence. [5][6][7][8][9] Additionally, in fresh ex-vivo experiments, our group showcased that the DOCI system reliably differentiates HNSCC from surrounding normal tissue and facilitates specific tumor localization [Figure 1]. 5 DOCI images are captured in real-time, do not require administration of contrast agents, and offer an operatively wide field of view.…”
Section: Introductionmentioning
confidence: 99%